PENDEKATAN KORELASI PEARSON DAN SPEARMAN DALAM MENGANALISIS HUBUNGAN PENGGUNAAN BAHAN AJAR BERBASIS DARING DAN PRESTASI AKADEMIK MAHASISWA - Sihotang, Siti Fatimah; Harahap, Fitrah Sari Wahyuni; Mazaly, Muhammad Rizky (MES: Journal of Mathematics Education and Science, 2024)
The rapid development of Science and Technology has now been widely used in various fields of life, especially in the field of education, specifically in the field of Mathematics. The increasing development of educational technology makes the use of online-based teaching materials an important component in the learning process in higher education. Of course, this is expected to influence the progress of student academic achievement. Therefore, researchers are interested in conducting research which aims to analyze the relationship between the use of online-based teaching materials and student academic achievement. The method used in this research involves analysis with two methods, namely Pearson and Spearman correlation. Both methods aim to measure the strength and direction of the relationship between two variables, namely the use of online teaching materials and student academic achievement. The Pearson correlation method is used for data that meets the normal distribution assumption, while the Spearman correlation is used for data that does not meet the normality assumption. The research sample was taken from students who actively used online teaching materials during one semester. The research results show that there is a significant relationship between the intensity of use of online-based teaching materials and student academic achievement. The Pearson correlation value shows a positive linear relationship between the two variables with a value of 0.744. Based on these findings, it can be concluded that the use of online-based teaching materials has strong potential to improve student academic achievement, with a significance value for the strength of the relationship between variables of 0.027.